Karakteristik Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di Kelas Rendah Sekolah Dasar - Nasrul Umam (Progressive of Cognitive and Ability, 2022)
This study aims to determine how the characteristics of PAI and Budi Pekerti learning in the lower grades of elementary school. This research includes literature study research. Researchers first conducted a study of several books, journals, proceedings, and others. Then connect the theory with PAI learning in low grades that have different characteristics. The results of the study, a) PAI and Budi Pekerti learning is faith-based which every adherent must believe; b) learning begins by linking concrete objects to deliver an understanding of abstract Islamic teachings; c) PAI learning materials should be arranged in an integrative way in one theme that includes PAI cluster subjects; d) Learning is carried out with simple learning materials to complex materials.